Branding dan Media Lokal: Strategi Komunikasi Pemasaran Pariwisata Sejarah di Aceh Besar - Khairina, Ulfa; Samaliah, Nur (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2025)
Aceh Besar is rich in mature tourist destinations that can be used as a source of creative economic growth for the community. In addition, the iconic historic tourism destination, Aceh Besar has many tourist destinations that can be branded through the use of local media. This study aims to further examine the use of local media in creating the historic tourism marketing communications in Aceh Besar. Data collection was conducted through interviews and participatory observation. The results show that the Aceh Besar Tourism and Youth Agency (DISPARPORA) does not build relationships with local media, but instead uses tourism ambassadors as spokespersons and outdoor media for each event. Meanwhile, local media brands promote tourism through articles produced as part of their support for tourism in Aceh Besar.